Emotional first aid practical strategies for treating failure, rejection, guilt, and other everyday psychological injuries - Winch, Guy (Hudson Street Press, 2014)
Prescriptive and unique, Emotional First Aid is essential reading for anyone looking to become more resilient, build self-esteem, and let go of the hurts and hang-ups that are holding them back. We all sustain emotional wounds. Failure, guilt, rejection, and loss are as much a part of life as the occasional scraped elbow. But while we typically bandage a cut or ice a sprained ankle, our first aid kit for emotional injuries is not just understocked-it's nonexistent.Fortunately, there is such a thing as mental first aid for battered emotions. Drawing on the latest scientific research and using real-life examples, practicing psychologist Guy Winch, Ph.D. offers specific step-by-step treatments that are fast, simple, and effective.